ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ruly Dewi Febriani, 12.05.52.0140; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of the Board of Independent Commissioners, Number BOC, Company Size, Leverage, Profitability, Capital Intensity Ratio, the effective tax rate on Food And Beverage Company Listed in Indonesia Stock Exchange. The population in this study were all Food and Beverage Yag company listed on the Indonesia Stock Exchange in the period 2011- 2014. This study is an empirical study by using purposive sampling technique in sampling. The analysis was performed by multiple regression using SPSS for windows version 19:00. The results showed that the Board of Independent Commissioners, Profitability positive and significant impact on the effective tax rate. The number of commissioners, company size and Capital intensity ratio does not affect the effective tax rate. Leverage a significant negative effect on the effective tax rate. Â Keywords: Independent Commissioner Board, Total BOC, Company Size, Leverage, Profitability, Capital Intensity Ratio and The Effective Tax Rate